TRENDS IN ISLAMIC EDUCATION RESEARCH IN THE SOCIETY 5.0 ERA: A SYSTEMATIC LITERATURE REVIEW - Slamet Riyadi; Nur Adilah; Suwardi Suwardi; Ikhwan Rahman (Journal of Social and Economics Research, 2026)
The development of digital technology in the Society 5.0 era is driving changes in Islamic Religious Education (IRE), in terms of the learning process, educators’ competencies and the use of technology. A variety of studies have been published, but these have not yet provided a comprehensive overview of research trends, key themes and research gaps. This article aims to analyse the direction of research development in Islamic Religious Education in the Society 5.0 era through a Systematic Literature Review (SLR) approach. The analysis was conducted in accordance with the PRISMA 2020 guidelines on articles obtained from Google Scholar, Garuda, Crossref, and Dimensions, published between 2023 and 2026. A total of 12 articles meeting the inclusion criteria were analysed thematically and supplemented with bibliometric analysis using VOS viewer. The results of the analysis indicate that publications on Islamic Religious Education in the Society 5.0 era have increased in recent years and are dominated by qualitative approaches and Systematic Literature Reviews. The VOS viewer analysis identified five main themes, namely the transformation of Islamic education, the transformation of digital technology-based learning, artificial intelligence, the development of research methods, and the development of the curriculum and Islamic values. The analysis also showed that research is still dominated by conceptual studies, whilst empirical research on the implementation of digital technology in Islamic Education (PAI) remains limited. These findings provide an insight into the direction of research development and serve as a basis for the development of more innovative and adaptive studies in Islamic Religious Education in the Society 5.0 era.